CHARACTERIZATION OF UREASE EXTRACTED UNDER THE OPTIMUM CONDITIONS FROM SOME LOCAL PLANT SEEDS - Osama H. Ali,; Mohanad J. M-Ridha,; Sahar I.H, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to determine the optimum conditions of urease extracted from different plant sources and evaluate its biochemical properties. Eighteen types of plants commonly used namely Tomato, Chickpea, Sesame, Mustard, Lebbeck, Watermelon, Soybean, Cotton, Male Iraqi berries, Female Iraqi berries, Indian berries, Pumpkin, Muskmelon, Legumes, Cowpea, Radish, Pisum and Phaseolus were taken and tested for the presence and activity of urease. Cotton (Gossypium barbadense) was selected as the plant source with highest specific enzymatic activity among them (2.51 U/mg protein) when extracted the enzyme after ground seeds using 0.15 M of tris base buffer pH 8.5 at a ratio 1:10 (w:v) for 15 min. Also the results showed that urease was stable in pH 8, and has the highest activity at 37 oC at 60 min of reaction time.          .